Implantable cardiac defibrillator leads dysfunction after LVAD implantation. Issue 11 (24th July 2020) - Galand, Vincent; Leclercq, Christophe; Bourenane, Hamed; Boulé, Stéphane; Vincentelli, André; Maury, Philippe; Mondoly, Pierre; Picard, François; Welté, Nicolas; Kindo, Michel; Cardi, Thomas; Pasquié, Jean‐Luc; et al.
Abstract: Background: Implantable cardioverter‐defibrillator (ICD) lead dysfunction has been reported after left ventricular assist device (LVAD) implantation in limited single‐center studies. We aimed at describing and characterizing the incidence of ICD lead parameters dysfunction after LVAD implantation. Methods: Among the 652 patients enrolled in the ASSIST‐ICD study, only patients with an ICD prior to LVAD were included (n = 401). ICD lead parameters dysfunction following LVAD implantation is defined as follows: (a) >50% decrease in sensing threshold, (b) pacing lead impedance increase/decrease by >100Ω, and (c) >50% increase in pacing threshold. Results: One hundred twenty‐two patients with an ICD prior to LVAD had available ICD interrogation reports prior and after LVAD. A total of 67 (55%) patients exhibited at least one significant lead dysfunction: 17 (15%) exhibited >50% decrease in right ventricular (RV) sensing, 51 (42%) had >100 Ω increase/decrease in RV pacing impedance, and 24 (20%) experienced >50% increase in RV pacing threshold. A total of 52 patients experienced ventricular arrhythmia during follow‐up and all were successfully detected and treated by the device. All lead dysfunction could be managed conservatively. Conclusion: More than 50% of LVAD‐recipients may experience >1 significant change in lead parameters but none had severe clinical consequences.